Uniqueness Of Solution To The Problem For One Mixed Integral-Differential Equation - Shahlo B. Merajova (Genius Journals, 2024)
In this article we consider integro-differential equations of mixed type. We prove the uniqueness of the solution.
Keywords: differential equations of mixed type, integro-differential equations, boundary value problem